An Analysis Of Islamic Banking Accounting Barriers In Samarinda City - Andi Fika Widuri; Nandang Ihwanudin; Nunung Nurhayati (Research Synergy Foundation, 2022)
Abstract At the age of 20 years of Islamic banking, it turns out that the existence of LKS cannot be separated from public criticism. Most of them still conclude that the mechanism of Islamic banking is no different from conventional, this condition must be straightened out. This study aims to analyze what are the main factors that hinder the development of Islamic banking accounting in Samarinda City. The research method used is a transcendental phenomenological approach, because the aim of the researcher is to explore the public's view of Islamic banking and Islamic accounting. Then, the informants were practitioners (managers of financial institutions), the standard setting board (DSAS) and academics (students from Mulawarman University). The practitioners chosen by the researchers were representatives from several macro-level Islamic commercial banks and several LKMS such as BPRS and BMT located in Samarinda City, East Kalimantan. From the results of the study, it was found that the stereotype of the public who thinks that Islamic accounting is not substantially different from conventional accounting is true. The fundamental problem that causes deviations from sharia practice from Islamic law is due to the human resource factor. Their lack of understanding and reluctance to understand sharia in a holistic manner makes the practice of sharia seen as the result of duplication of conventional accounting. Key Word: Islamic Banking, Islamic Banking Accounting, Inhibiting Factors of Islamic Accounting